The relationship between Insulin‐like Growth Factor 1, sex steroids and timing of the pubertal growth spurt. (8th January 2015) - Cole, T.J.; Ahmed, M.L.; Preece, M.A.; Hindmarsh, P.; Dunger, D.B.
Summary Objective Progress through puberty involves a complex hormonal cascade, but the individual contributions of hormones, particularly IGF‐1, are unknown. We reanalysed Chard growth study data to explore the tempo of puberty based on changes in both height and hormone levels, using a novel method of growth curve analysis. Design and Subjects Schoolboys (n = 54) and girls (n = 70) from Chard, Somerset, England, recruited in 1981 at age 8/9 and followed to age 16. Measurements Every 6 months, height and Tanner stages (genitalia, breast, pubic hair) were recorded, and in a subsample (24 boys, 27 girls), blood samples were taken. Serum IGF‐1, testosterone (boys) and oestradiol (girls) were measured by radioimmunoassay. Individual growth curves for each outcome were analysed using variants of the super‐imposition by translation and rotation (SITAR) method, which estimates a mean curve and subject‐specific random effects corresponding to size, and age and magnitude of peak velocity. Results The SITAR models fitted the data well, explaining 99%, 65%, 86% and 47% of variance for height, IGF‐1, testosterone and oestradiol, respectively, and 69–88% for the Tanner stages. During puberty, the variables all increased steeply in value in individuals, the ages at peak velocity for the different variables being highly correlated, particularly for IGF‐1 vs height (r = 0·74 for girls, 0·92 for boys). Conclusions IGF‐1, like height, the sex steroids and Tanner stages, rises steeply in individuals during puberty, with the timings of the rises tightly synchronized within individuals. This suggests that IGF‐1 may play an important role in determining the timing of puberty.